2001
DOI: 10.1897/1551-5028(2001)020<2725:bobaia>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Bisphenol a in Aquatic Environments: River Die-Away

Abstract: The biodegradability of bisphenol A (BPA) was assessed in surface waters from seven different rivers across the United States and Europe. Rapid biodegradation of BPA was observed in all rivers following lag phases ranging from 2 to 4 d. Biodegradation half-lives for BPA were typically less than 2 d following the lag phase. Mineralization of BPA was observed in all river waters, with average carbon dioxide yields of approximately 76% of the theoretical maximum (range 59-103%) at the end of the incubation period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 5 publications
(8 reference statements)
11
45
0
Order By: Relevance
“…It is difficult to accurately estimate uptake efficiency for both compounds in the root exposure treatments due to their instability in the hydroponic system. Previous studies have reported that BPA and NP can quickly degrade in aqueous and soil environments due to microbial action [20,30], similar to this study. Ignoring the instability issue, the total mass uptake ranged from 0.002% (tomatoes) to 0.02% (lettuce, BPA) and 0.07% (lettuce, NP) of the total amount of both contaminants applied to both crops, with roots containing the highest concentrations of each.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is difficult to accurately estimate uptake efficiency for both compounds in the root exposure treatments due to their instability in the hydroponic system. Previous studies have reported that BPA and NP can quickly degrade in aqueous and soil environments due to microbial action [20,30], similar to this study. Ignoring the instability issue, the total mass uptake ranged from 0.002% (tomatoes) to 0.02% (lettuce, BPA) and 0.07% (lettuce, NP) of the total amount of both contaminants applied to both crops, with roots containing the highest concentrations of each.…”
Section: Discussionsupporting
confidence: 89%
“…For the root exposure treatment, BPA and NP were spiked directly into the hydroponic nutrient solution. BPA and NP can be degraded efficiently by microflora in aqueous and soil environments, with half-lives of 1d or less [20,30]. This short half-life was confirmed in the hydroponic system used in the current study based on several monitoring events using an HPLC equipped with a fluorescence detector (Waters Corporation, Milford, MA).…”
Section: Exposuressupporting
confidence: 57%
“…The DT 50 -values determined in this experiment correspond well to data reported in the literature (Staples et al, 1998;Ike et al, 2000;Kle´cka et al, 2001). Also the observed lag-phase, after which the rapid disappearance of BPA from the water started, has been observed in other biodegradation tests with BPA (Ike et al, 2000;Kle´cka et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…However, no such positive relationship between the biomass amount and BPA degradation was observed in seawater. The difference may be due to the size of bacterial cell counts that can perform the fast and complete BPA degradation, or due to the existence of other chemical degradation of BPA, such as degradation by reactive oxygen species, in seawater (Klecka et al 2001;Yonokubo 2002, 2003;Kang and Kondo 2005;Zhang et al 2007). The substrate concentration was another factor that affected BPA degradation.…”
Section: Bpa Degradation By Gram-negative Bacteriamentioning
confidence: 99%